FAUNISTIC CHARACTERISTICS AND SPECIES COMPOSITION OF BLOODSUCKING MOSQUITOES (DIPTERA, CULICIDAE) IN THE REPUBLIC DAGHESTAN - Sadaget S. Gadzhieva (Юг России: экология, развитие, 2018)
Aim. The main aim of the research is to study the conditions of existence and the timing of the development of the preimaginal and imaginal phases of blood-sucking mosquitoes, depending on the natural and climatic conditions. Methods. Adult species were collected at the roost sites and at the time of swarming with the use of scoop net every five days throughout the season. The larval phases of bloodsucking mosquitoes were taken into account in all given reservoirs of various types using a photocell. Discussion. The results of the study showed that in the study area, the largest region where mosquitoes are reproduced is mainly artificial reservoirs accounting for approximately 65%, natural water bodies (25%) and hollows of tree trunks (10%). The saturation of the larvae of the malarial mosquito of the genus Anopheles was 82 species/m2, non malaria mosquitoes of the genus Culex – 234 species/m2, while Aedes genus made up 105 species/m2. Conclusion. There are 19 species of mosquitoes inhabiting Dagestan. The development of preimaginal and imaginal phases of blood-sucking mosquitoes on the territory of Dagestan is ecologically diverse.